2021
DOI: 10.1055/s-0041-1722964
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Management of the Post–Pulmonary Embolism Syndrome

Abstract: Acute pulmonary embolism (PE) is not only a serious and potentially life-threatening disease in the acute phase, in recent years it has become evident that it may also have a major impact on a patient's daily life in the long run. Persistent dyspnea and impaired functional status are common, occurring in up to 50% of PE survivors, and have been termed the post-PE syndrome (PPES). Chronic thromboembolic pulmonary hypertension is the most feared cause of post-PE dyspnea. When pulmonary hypertension is ruled out,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 100 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…The PPES is defined as new or progressive dyspnoea, exercise intolerance, and/or impaired functional or mental status after at least 3 months of adequate anticoagulation following acute PE, which cannot be explained by other (pre-existing) comorbidities. 34 , 35 It is reported in up to 40–60% of PE survivors. Incomplete thrombus resolution occurs in 25–50% of patients after acute PE despite adequate anticoagulation, but bears no clinical significance in most cases.…”
Section: Post-pulmonary Embolism Syndromementioning
confidence: 99%
“…The PPES is defined as new or progressive dyspnoea, exercise intolerance, and/or impaired functional or mental status after at least 3 months of adequate anticoagulation following acute PE, which cannot be explained by other (pre-existing) comorbidities. 34 , 35 It is reported in up to 40–60% of PE survivors. Incomplete thrombus resolution occurs in 25–50% of patients after acute PE despite adequate anticoagulation, but bears no clinical significance in most cases.…”
Section: Post-pulmonary Embolism Syndromementioning
confidence: 99%
“…21 Decreased daily physical activity after a PE diagnosis with resulting physical deconditioning is one of the main explanations for post-PE functional impairment. 11 18 19 20 43 44 In addition, persistent thoracic pain, anxiety, and postthrombotic panic syndrome, as well as fear for recurrences or complications, contribute largely to functional limitations, on both the social and professional level. 45 46 47 Post-PE functional impairment is associated with reduced QoL and higher prevalence of depression and permanent work-related disability.…”
Section: The Post-pe Syndromementioning
confidence: 99%
“…As discussed above, CTEPH is the most severe diagnosis on a spectrum of long-term complications that can arise after the diagnosis of acute PE. 19,21,42,43 It is unknown whether this spectrum of disease exists as a progressive continuum versus a group of related disease processes after acute PE. While the incidence of CTEPH after acute PE episode is between 0.1% and 9.1%, multiple studies have reported that up to 50% of patients experience residual pulmonary symptoms or exercise/functional limitations after acute PE, thus bringing about the entity of the PPES, which includes CTEPH, CTED, post-PE cardiac impairment and post-PE functional impairment.…”
Section: Epidemiology Of Cteph the Post-pe Syndromementioning
confidence: 99%